An overview of valuation practices and the development of a Canadian code for the valuation of mineral properties - K. Spence (Canadian Institute of Mining, Metallurgy and Petroleum, 2002)
"The notion of “value” has always been a subjective and contentious issue. Indeed, value is in the eye of the beholder. There are as varied methods and practices for valuing property, as there are industries in which they are applied. For example, there is replacement value, insurance value, salvage value, appraised value, book value, and fair market value, to name a few, although in the mining industry, valuations usually refer to fair market value.In the Canadian mining industry, at present, there are no comprehensive regulations or guidelines that specify which approaches or methods are appropriate for use in the valuation of mineral projects. In January 1999, The Mining Standards Task Force of the Toronto Stock Exchange and the Ontario Securities Commission recommended that the Canadian Institute of Mining, Metallurgy and Petroleum (CIM) establish a committee to review and advise on approaches and methodologies for the valuation of mineral properties. Among the approaches to be considered are included the following: the discounted cash flow approach, the cost approach, the option pricing approach and the market comparables approach. In addition, methodologies differ depending on whether the project is at the exploration stage or the producing stage.The CIM Special Committee on the Valuation of Mineral Properties (CIMVal) expects that its final report will form the basis for a Canadian code or standard for the valuation of mineral properties."